THE EFFECT OF EQUIPMENT MAINTENANCE PERFORMANCE ON PRODUCTION QUALITY IN THE EGR SECTION OF PT ABC (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effect of Equipment Maintenance Performance on Production Quality in the EGR Section of PT ABC. A quantitative approach was employed using a survey method by distributing questionnaires to employees directly involved in production processes, equipment maintenance, and quality control activities. The population consisted of 72 employees from the EGR Assembly, EGR Machining, Maintenance, and Quality Control departments. A total sampling technique was applied; therefore, all members of the population were included as research respondents. The data were analyzed using validity testing, reliability testing, classical assumption testing, simple linear regression analysis, t-test, and coefficient of determination with the assistance of SPSS version 26. The results indicate that Equipment Maintenance Performance has a positive and significant effect on Production Quality. This finding is supported by the regression equation Y = -16.674 + 0.863X, the calculated t-value of 12.347, which exceeds the critical t-value of 1.994, and a significance value of 0.000 < 0.05. The R Square value of 0.685 indicates that Equipment Maintenance Performance explains 68.5% of the variation in Production Quality, while the remaining 31.5% is influenced by other factors outside the scope of this study. These findings suggest that effective equipment maintenance plays an important role in maintaining process stability, machine readiness, and the conformity of production outputs to company standards.